Strategi Pemberdayaan Ekonomi Masyarakat Melalui Peningkatan Nilai Jual Telur Puyuh Program CSR PT Pertamina Integrated Terminal Cilacap bersama BNNK Cilacap di Desa Slarang - Asriati Alifah; Azis Wahyono (CV. ITTC INDONESIA, 2026)
Village economic empowerment is a crucial effort to improve community welfare and independence based on local potential. Slarang Village, Cilacap Regency, has economic potential in quail farming, managed by the community through the RAI BERSINAR Group. Although quail egg production is relatively stable, its utilization is not optimal because most are still sold raw with a relatively low selling price. This article aims to examine strategies for increasing the selling value of quail eggs through the development of processed products and their impact on the economic empowerment of the village community. This research uses a qualitative descriptive approach with data collection techniques through interviews and observations of quail farmers and PKK members in Slarang Village, PLUT and DPKUKM. The results of the study indicate that strategies for increasing selling value are implemented through innovations in processed products such as braised quail eggs and quail egg floss, improvements in packaging systems, and expansion of offline and digital marketing. This strategy not only increases product added value but also encourages community participation, strengthens group cooperation, and fosters a collective-based entrepreneurial spirit. With ongoing mentoring, the development of a quail egg processing business has the potential to become a means of economic empowerment for the Slarang Village community, leading to independence and sustainability.